Magnetic-Guided Capsule Endoscopy in the Diagnosis of Gastrointestinal Diseases in Minors - Yuting Qian; Tingting Bai; Juanjuan Li; Yi Zang; Tong Li; Mingping Xie; Qi Wang; Lifu Wang; Ruizhe Shen (Gastroenterology Research and Practice)
Objective. This study aimed at investigating the clinical value of magnetic-guided capsule endoscopy (MGCE) in the diagnosis of gastrointestinal diseases in minors. Methods. Eighty-four minor patients hospitalized in the pediatric department at Ruijin Hospital between June 2015 and January 2018 were enrolled for this study. Following bowel preparation, all patients underwent MGCE. The feasibility, safety, diagnostic yield, and sensitivity of MGCE were analyzed. Patients were followed up for more than 2 weeks. Results. The main indications for MGCE in minors were Crohn’s disease, gastrointestinal bleeding, and abdominal pain. The main causes of gastric disease were gastric inflammatory hyperplasia, exudative gastritis, and polyps. The most common small bowel diseases in minors were Crohn’s disease, Henoch-Schonlein purpura, and polyps. The diagnostic yield in the stomach and small intestine was 13.1% and 28.6%, respectively, and the sensitivity was 100% and 96.0%, respectively. No adverse events occurred. Conclusion. MGCE is a safe, effective, and well-tolerated procedure with good sensitivity and has a potential clinic value for the diagnosis of gastrointestinal diseases in minors.